Characterization of Mild Thermal Stress in Pseudomonas fluorescens and Its Repair - Gray, Rodney J. H. (1973)
The exposure of exponentially growing Pseudomonas fluorescens P7 cells to heating at 36 C for 2 h in a defined medium, followed by cooling to 25 C and further incubation at this, the optimal growth temperature, resulted in the apparent death of approximately 99% of the cells, as determined by their inability to form colonies on Trypticase soy agar. Continued incubation at 25 C resulted in an extremely rapid increase in the Trypticase soy agar count, demonstrating that the phenomenon observed was not death but rather injury. Presumptive evidence of heat-stimulated ribonucleic acid (RNA) degradation and membrane damage was provided by the observed loss of 260-nm absorbing materials. Confirmation of RNA degradation was obtained by colorimetric analysis. Ribosomal RNA from normal and injured cells, which was electrophoretically separated on polyacrylamide gels, revealed that the 23S and 16S species were only partially destroyed. Inhibitor studies demonstrated, however, that RNA synthesis was necessary for recovery. The unusual accumulation of 17S RNA during recovery pointed to the presence of a heat-induced lesion in the RNA maturation process. A thermally induced membrane lesion is also discussed.